The Application Construction of Fala Kanci as Healthy House for The Future - Andriani Tiara Puput; Marasabessy Firdawaty; Muhammad Asri A (MATEC Web of Conferences, 2022)
House is everything during the current Covid-19 pandemic. The house does not only function as a place to live, but more than that it is used for work, study, sports, and others. The concept of a healthy home that must be presented during this pandemic cannot be separated from the washing of health protocols, namely an optimized natural ventilation system, the availability of isolation rooms in each home, and the provision of hand sanitizing facilities (washtafel). The concept of structuring houses in traditional houses in North Maluku is following the concept of the current health protocol. Considering that the concept of traditional houses, especially people's houses, in several aspects are following health protocols, for this reason, it is necessary to model a healthy house after the Covid-19 pandemic to get a decent healthy house as a mitigation effort from biological disasters. The purpose of this study was to observe traditional houses that apply the principles of health protocols and the basics of these houses in the form of concept drawings.The result of the research is to make a new prototype to be modeled by considering natural ventilation systems, social distancing, and sanitation systems.